2021
DOI: 10.17576/jsm-2021-5001-14
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Copper, Iron, and Nickel Doped Titanium Dioxide Photocatalysts for Decolorization of Methylene Blue

Abstract: The visible-light response is a necessary condition for titanium dioxide (TiO2) photocatalyst to function as a visible light active photocatalyst. This condition can be solved by investigation of the bandgaps and the optimization of doping levels of multivalency metal-doped TiO2. In this study, pure and Cu, Fe, and Ni-doped TiO2 photocatalysts were prepared by the sol‐gel method. The photocatalysts were characterized using XRD, FTIR, FESEM, EDX, N2 physisorption, and UV‐Vis spectrophotometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The surface morphology for freshly coated and 50 times recycled beads were almost the same. From FESEM/EDAX analysis, this can be concluded that the composite beads are very efficient and can be used for commercial‐scale applications (Qaderi et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The surface morphology for freshly coated and 50 times recycled beads were almost the same. From FESEM/EDAX analysis, this can be concluded that the composite beads are very efficient and can be used for commercial‐scale applications (Qaderi et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…An activated carbon (AC) act as a supporting material for TiO2 due to their large surface area and developed pore structures [11]. TiO2 doping with transition metals such as Cu have been widely investigated because they are more earth-abundant, affordable, and less toxic than noble metals [12]. However, there is limited study on the optimization for synthesizing process of AC/TiO2-Cu.…”
Section: Introductionmentioning
confidence: 99%